Power‐take‐off topology comparison for a wave energy converter. Issue 18 (3rd July 2019) - McDonald, Stephen P.; Baker, Nick J.; Espinoza, Mauricio; Pickert, Volker
Abstract : Wave Energy Converters (WECs) generally use a Mechanical Power‐Take‐Off (MPTO) involving hydraulics or gearing to optimise the extraction of energy from the incoming waves before converting it into electrical energy via a high speed rotating generator. This simplifies the design of the Electrical Power Conversion System (EPCS). Further, it facilitates the use of mechanical energy storage such as hydraulic accumulators to reduce the peaky nature of the power flow and allows the WEC resonant frequency to be tuned for maximum energy capture. This work compares two power electronic converter topologies for an Electrical PTO (EPTO). This EPTO is intended to replace the aforementioned MPTO and generator with a Permanent Magnet Linear Machine (PMLM) directly coupled to the WEC. The compared topologies comprise either a Current Source Converter (CSC) or a Voltage Source Converter (VSC) as the generator interface working in combination with a DC‐DC converter and an Energy Storage System (ESS). The principle differences between the two topologies are explored and losses are evaluated in a modular EPCS working with a WEC. Wide‐bandgap power electronic switches are assumed for both topologies over a range of switching frequencies. The evaluation concludes that the CSC topology is advantageous at higher switching frequencies.